Theory-driven group-based complex intervention to support self-management of osteoarthritis and low back pain in primary care physiotherapy: protocol for a cluster randomised controlled feasibility trial (SOLAS). Issue 1 (21st January 2016) - Hurley, Deirdre A; Hall, Amanda M; Currie-Murphy, Laura; Pincus, Tamar; Kamper, Steve; Maher, Chris; McDonough, Suzanne M; Lonsdale, Chris; Walsh, Nicola E; Guerin, Suzanne; Segurado, Ricardo; Matthews, James; et al.
Abstract : Introduction: International clinical guidelines consistently endorse the promotion of self-management (SM), including physical activity for patients with chronic low back pain (CLBP) and osteoarthritis (OA). Patients frequently receive individual treatment and advice to self-manage from physiotherapists in primary care, but the successful implementation of a clinical and cost-effective group SM programme is a key priority for health service managers in Ireland to maximise long-term outcomes and efficient use of limited and costly resources. Methods/analysis: This protocol describes an assessor-blinded cluster randomised controlled feasibility trial of a group-based education and exercise intervention underpinned by self-determination theory designed to support an increase in SM behaviour in patients with CLBP and OA in primary care physiotherapy. The primary care clinic will be the unit of randomisation (cluster), with each clinic randomised to 1 of 2 groups providing the Self-management of Osteoarthritis and Low back pain through Activity and Skills (SOLAS) intervention or usual individual physiotherapy. Patients are followed up at 6 weeks, 2 and 6 months. The primary outcomes are the (1) acceptability and demand of the intervention to patients and physiotherapists, (2) feasibility and optimal study design/procedures and sample size for a definitive trial. Secondary outcomes include exploratory analyses of: point estimates, 95% CIs, change scores and effect sizes in physical function, pain and disability outcomes; process of change in target SM behaviours and selected mediators; and the cost of the intervention to inform a definitive trial. Ethics/dissemination: This feasibility trial protocol was approved by the UCD Human Research Ethics—Sciences Committee (LS-13-54 Currie-Hurley) and research access has been granted by the Health Services Executive Primary Care Research Committee in January 2014. The study findings will be disseminated to the research, clinical and health service communities through publication in peer-reviewed journals, presentation at national and international academic and clinical conferences. Trial registration number: ISRCTN 49875385; Pre-results.